New Perspectives for Vulnerable Institutions: Agricultural Research Systems in the Small Countries of West Africa - Gilbert, Elon; Matlon, Peter; Eyzaguirre, Pablo B. (International Service for National Agricultural Research, 1994)
This paper reviews the policy and organizational constraints to agricultural research in nine small West African countries. These small countries cannot afford research institutions that can adequately cover the priority areas for agricultural R&D. Their small size, limited resources, and broad scope make these institutions particularly vulnerable. The authors explore the emerging regional paradigm, and new research partnerships. Building on these new developments and placing greater emphasis on functions including the management of human resources, external linkages and policy advice can enable small national research systems to survive and make important contributions to agricultural and natural resource research in West Africa.